JURISDICTIONAL CYBERCRIME CRIMINALIZATION POLICY IN THE USE OF INFORMATION TECHNOLOGY - Aprita, Serlika; Hanif, Wangmayum (Sriwijaya Crimen and Legal Studies, 2024)
The victim and the offender are frequently in separate nations, a crime known as cybercrime transcends all borders and periods. Cybercrime can be committed using the computer itself as the method of committing the crime and the computer network system as the target. Laws governing information technology must take into account its rapid growth. Information and communication technology laws must anticipate and lessen these negative consequences. For information, media, and communication technology to progress as much as possible, legal products about cyberspace, or mayantara, must offer security and legal certainty. In response to the increasing number of cybercrimes, the government adopted a policy on April 21, 2008, with the adoption of Law No. 11 of 2008 regarding Information and Electronic Transactions (UU ITE). The ITE Law is Indonesia's first legislation focusing on online regulation. Based on the research findings, it can be concluded that Indonesian law enforcement has been unable to combat cybercrime to the best of its abilities. Indonesian law enforcement is facing difficulties due to the growth in cybercrime. The reasons for this are a lack of public legal awareness in efforts to combat information technology crimes, limited facilities and infrastructure, and the fact that there are still relatively few law enforcement officials who are familiar with the ins and outs of information technology (internet).